The Human Rights and Development Impetuses for Tunisia's Jasmine Revolution. (March 2014) - Alvi, Hayat
Economics Nobel laureate Amartya Sen contends that socio-economic progress cannot happen without freedoms. The thesis for this article is that human rights and development variables, which were appalling under the Ben Ali regime, served as primary causal factors for the 2011 Tunisian Revolution. Dismal human development indicators, rampant corruption and severe repression of freedoms and rights led to widespread protests. Other regional actors also felt inspired by the Tunisian Revolution, culminating in uprisings and revolutions in neighboring countries. This analysis examines the human rights and development impetuses for Tunisia's Jasmine Revolution. The central questions to address are: What are the linkages between human rights, freedoms, and human development in Tunisia? What made Tunisian activists overcome their fear of the regime? And, what are the implications of the post-revolution political, ideological and economic policies and dynamics for the country's socio-economic progress?